Spatiotemporal dynamics and prediction of land use and land cover changes under seismic hazard: a case study of the Oran region, Algeria - Rahal, Farid; Baba-Hamed, Fatima-Zohra (Acta Geographica Lodziensia, 2025)
Seismic hazard cannot be understood solely as an exogenous threat. It is part of a broader urban dynamic. The city of Oran is a telling example, its expansion being highlighted through the study of land use and land cover (LULC) trends based on a time series of Landsat satellite images from 2015 to 2025 with a five-year interval. Over the past 15 years, the study area has experienced a significant increase in built-up area, increasing from 9.59% to 13.83%, while vegetation cover has decreased from 21.65% to 16.56%. Furthermore, predictions (2030–90) confirm the growing trend towards artificialization of surfaces. The relationship between urban growth and seismic hazard is important to examine. Indeed, the overlay of maps of predicted urban growth and those of seismic wave amplification zones showed that there will be a sharp increase in the level of urbanization in areas representing a medium seismic hazard.